Persahabatan merespon tanda-tanda zaman (analisis historiografis duc in altum kolaborasi stft widya sasana) - FX. EKO ARMADA RIYANTO (Seri Filsafat Teologi, 2020)
This article focuses on the theme of collaboration and friendship lived and experienced in Widya Sasana School of Philosophy and Theology to respond the challenges of the times. The methodology applied is analysis of historical moments without going into the details of the events based on the original documents of foundation of the campus. The goal of study is to analize how friendship and collaboration have shaped and built up this campus. STFT Widya Sasana is metaphorically like a ship that has to continue to sail across the ocean of educational challenges from time to time. This historiographical analysis study found that true friendship needs to prioritize missionary, collaborative, dialogical, accountable and sustainable characters for the priestly education in such a way that the alumni be able to respond to the challenges of the times.